IMPLEMENTASI 7 KEBIASAAN ANAK INDONESIA HEBAT (KAIH) DALAM MENINGKATKAN KARAKTER RELIGIUS SISWA SMPN 8 PAMEKASAN - Syaifurrahman Nabawi; Mad Sa’i (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of the 7 Habits of Great Indonesian Children (KAIH) program in strengthening students’ religious character at SMPN 8 Pamekasan. The research focuses on the implementation process, habituation strategies, and the program’s influence on students’ religious attitudes in both learning activities and school life. The aim of this study is to analyze the implementation of KAIH and to identify changes in students’ religious character following its consistent application. A qualitative approach with a case study design was employed. Data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction, data display, and thematic conclusion drawing. The findings indicate that KAIH is integrated into intracurricular activities, co-curricular programs, and school culture. The habituation process enhances students’ discipline in worship, polite behavior, responsibility, and social awareness. The program also strengthens teachers’ roles as character role models. This research contributes theoretically to the development of habit-based religious character education and practically offers an applicable KAIH implementation model for junior secondary schools.